Two-Year Comparative Outcomes of MIS Lateral and MIS Transforaminal Interbody Fusion in the Treatment of Degenerative Spondylolisthesis: Part II: Radiographic Findings. (April 2016) - Isaacs, Robert E.; Sembrano, Jonathan N.; Tohmeh, Antoine G.
Abstract : Study Design: Prospective, multicenter, institutional review board approved study with randomized and observational study arms. Objective: The purpose of this study was to compare radiographic outcomes between minimally invasive transforaminal (MIS TLIF) or MIS lateral interbody fusion (XLIF) in the treatment of patients with low-grade degenerative spondylolisthesis with stenosis through 2-year postoperative. Summary of Background Data: Few reports exist comparing different MIS approaches directly in the treatment of similar pathology, as most studies report differences between MIS and open procedures. Methods: A total of 55 patients undergoing surgical treatment for degenerative spondylolisthesis with spinal stenosis at one or two contiguous levels between L1 and L5 were enrolled. Twenty-nine patients were treated with XLIF and 26 patients were treated with MIS TLIF. Results: Disc height was significantly improved from preoperative at all postoperative time points in both groups, though the XLIF group experienced less subsidence and resultant loss of disc height than the MIS TLIF group by 24-month postoperative ( P  = 0.002). Postoperative change in central canal area was statistically greater in the MIS TLIF compared with the XLIF group (43.1 mm 2 vs. 4.1 mm 2, P  = 0.028). At several postoperative time points, foraminal height and area on the ipsilateral side and foraminal height on the contralateral side to the approach were significantly increased postoperatively in the XLIF group, and the magnitude of ipsilateral height increase was greater than in the MIS TLIF cohort ( P  < 0.05). Using fusion criteria of <3° range of motion and <3 mm translation on plain radiographs, 100% of patients in both groups were solidly fused at 24-month postoperative. Using computed tomography fusion criteria of presence of intervertebral bridging bone, 100% (32/32) of XLIF levels and 96% (25/26) of MIS TLIF levels were solidly bridged ( P  = 0.448). Conclusion: Different mechanisms of stenosis correction (direct vs. indirect) between the MIS TLIF and XLIF groups studied resulted in several significantly different radiographic characteristics. Despite these differences, both groups of patients experienced significant and maintained clinical improvements with high fusion rates at 2-year follow-up, suggesting that the mechanism of correction may not be critical and both MIS procedures are reasonable treatment options for degenerative spondylolisthesis with stenosis. Level of Evidence: 2